Elaboración de un programa en JAVA para diseño de la viga principal y selección de elementos mecánicos para puentes grúa de capacidad hasta 50 toneladas y luz entre 3 y 30 metros con vigas tipo cajón - Ayala Herrera, Álvaro Mauricio (2018)
When designing an electronic overhead travelling crane, a lot of effort and time are spent. Therefore, the main aim of this work is to develop a box girder design software to ease the calculation of EOT cranes with a maximum capacity of 50 tons. The calculation methods used were based on the structural guidelines of the Crane Manufacturers Association of America specifications #70 and #74 for double and single cranes, respectively. In the initial phase of this project, methods to calculate the geometric properties of built-up beams were studied, as well as box-girder-design criteria, such as criteria of strength, torsion, local stability of plates, lateral stability of the girder, stiffness, Von Mises stress, etc. Furthermore, criteria for the proper selection of the main mechanical elements of an EOT crane were studied. In the second phase of this project, an illustrative design of the main girder of a double-girder crane was carried out. Loads exerted by trolley wheels were considered individually and not as a single concentrated load in order to minimize the fluctuation of results in regard to the real values. The shear, bending moment, and deflection equations were deduced using principles, such as the double integration method. Eventually, these equations were maximized to determine the critical values. The third phase consisted of writing the program using the JAVA programming language, and to implement databases using MySQL Workbench in order to enable the selection of the mechanical elements. Finally, the program was tested, and the obtained results were compared to simulations in both SAP2000 and SolidWorks. The comparison of values resulted in small error percentages, which guarantee the accuracy and reliability of the program.